A Upaya Pengenalan Kebudayaan Sumatera Utara Melalui PMM3 Pada Mata Kuliah Modul Nusantara di Universitas HKBP Nommensen Medan - Fransiska, Rela Melda; Pristiani, Yunita Dwi; Simarmata, Rina Octavia; Nursalim, Nursalim; Suratman, Suratman; Sasmita, Wikan (Universitas Nusantara PGRI Kediri, 2024)
Indonesia has various tribes and cultures, from Sabang to Merauke. Culture in Indonesia is known as a view of values ​​in social life. North Sumatra is one of the provinces in Indonesia which is famous for its cultural diversity among the 38 provinces in the country. This research aims to determine efforts to introduce culture in the province of North Sumatra through the PMM3 program in the Archipelago course at HKBP Nommensen University, Medan. This research is a type of qualitative research. Introduction to Culture for PMM3 students in 3 ways: education, religion and culture. Introduction efforts were made through learning, visiting the Maytreya monastery, enjoying the Sigale-gale dance performance, and visiting the Ulos village. Based on the research results, it is known that PMM3 students have additional knowledge and insight into culture in the province of North Sumatra obtained from experience and learning the Nusantara module.